So.Be.DidLab: the perception of environmental risks and well-being in school contexts - Giuseppa Cappuccio; Lucia Maniscalco (Firenze University Press, 2024)
According to Agenda 2030, the school, focusing on sustainability and well-being, aims at achieving a quality learning pathway, activating a deep cultural transformation for future education. Sustainable education should be integrated into all disciplines and promote a collective vision of sustainability. Measurement tools to assess and identify sustainability and well-being's factors, within the school context and, specifically, the workshop context, are essential for school to carry out educational-didactic actions. This paper presents the results of the survey "So.Be.Didlab: Sustainability, Well-being and Didactics Lab" aimed at identifying the main factors that influence the achievement of well-being within the school environment and how this can be extended to different areas of students' lives. The questionnaire was addressed to 507 teachers and 1543 students in Sicily.   So.Be.DidLab: la percezione dei rischi ambientali e della condizione di benessere nei contesti scolastici. Secondo l'Agenda 2030, la scuola volta alla sostenibilità e al benessere mira al raggiungimento di un percorso di apprendimento di qualità, attivando una trasformazione culturale profonda per l'educazione del futuro. L'educazione sostenibile dovrebbe essere integrata in tutte le discipline e promuovere una visione collettiva della sostenibilità. Disporre di strumenti di misura per valutare e individuare i principali fattori che determinano la sostenibilità e il benessere all'interno del contesto scolastico e, nello specifico, di quello laboratoriale, è essenziale per l'implementazione, nelle scuole, di azioni educativo-didattiche. Il presente lavoro espone gli esiti dell'indagine "So.Be.Didlab: Sostenibilità, Benessere e Didattica Laboratoriale" finalizzato a individuare i principali fattori che influenzano il raggiungimento del benessere all'interno dell'ambito scolastico e come questo possa estendersi a diversi ambiti della vita degli studenti. Il questionario è stato rivolto a 507 docenti e a 1543 studenti del territorio siciliano.